Konfigurasi Politik UU Cipta Kerja, Dan Implementasi Putusan MK Nomor 35/PUU-X/2012: Masa Depan Kedaulatan Atas Penguasaan Hutan Adat - Gusman, Delfina; Raspati, Lucky (Faculty of Law, Andalas University, 2024)
This paper aims to describe the implications of the legal-political configuration of the Job Creation Law and the implementation of Constitutional Court Decision Number 35/PUU-X/2012. The data used in this study are legal materials in the form of writings published by previous researchers related to the object of this study, and materials in the form of laws and Constitutional Court decisions. These primary and secondary materials will be analyzed and interpreted qualitatively. This study finds that the Job Creation Law is an orthodox legislation formed by an authoritarian political configuration that has undermined the mandate of Constitutional Court Decision Number 35/PUU-X/2012 and has implications for the constitutional rights of customary law communities by revoking their constitutional rights over their customary forests.